Memory and Emotion : Interdisciplanary Perspectives. - Uttl, Bob; Siegenthaler, Amy L.; Ohta, Nobuo (Australia, Blackwell, 2006)
Memory and Emotion: Interdisciplinary Perspectives is a collection of original articles that explores cutting-edge research in memory and emotion, discussing findings, methodological techniques, and theoretical advances in one of the fastest-growing areas in psychology.:.; contains contributions by leading researchers the field.; emphasizes cognitive neuroscience, psychopathology, and aging in covering contemporary advances in research on memory and emotion.; covers many of the current hot topics in the field including: dissociative amnesia and post-traumatic stress disorder; false, recovered.
Include Bibliography Reference and Index Material.
Keywords: Behavioral Sciences; Biological Science Disciplines; Behavioral Disciplines and Activities